Long lifespan and substantial biomass production support stable high biomass of Ascophyllum nodosum under interannual climate fluctuations in Greenland - Olesen, Birgit (Journal of phycology, 2025)
© 2025 The Author(s). Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.